Leveraging laser powder bed fusion to alter texture and mechanical properties of magnesium alloy WE43 - Lisa Larsson; Francesco D’Elia; Martin Sahlberg; Cecilia Persson (Materials & Design, 2025)
The present work explored the potential of customizing the final part texture and mechanical properties of a biodegradable magnesium alloy (WE43, composition Mg-4 wt%Y-3 wt%Nd-0.5 wt%Zr) manufactured by laser beam powder bed fusion (PBF-LB). This was done by printing samples using two sets of laser scan strategies (67⁰ and 90⁰ rotation between consecutively scanned layers) and build directions (horizontal and vertically printed samples). Samples were characterized for density and microstructure, followed by in-depth texture analysis using both lab-based techniques and neutron diffraction measurements. The mechanical performance was evaluated through tensile testing. The findings in this work show that strong basal texture was generated in the build direction. This allowed for altering the mechanical strength of WE43, whereby horizontally built samples showed increased strength and Young’s modulus under tensile loading in a direction normal to the basal texture. Laser scan strategy influences the overall texture, however with limited effect on the resulting mechanical properties for the two scan strategies under study. This study demonstrates the importance of sample design and build strategy for the resulting texture and final material properties.